Efficacy of the Dapivirine Vaginal Ring Accounting for Imperfect Adherence. - Husnik, Marla J.; Heffron, Renee; Hughes, James P.; Richardson, Barbra; van der Straten, Ariane; Palanee-Phillips, Thesla; Soto-Torres, Lydia; Singh, Devika; Mirembe, Brenda Gati; Livant, Edward; Gaffoor, Zakir; Mansoor, Leila E.; et al. (AIDS & Behavior, 2024)
Product adherence is critical to obtaining objective estimates of efficacy of pre-exposure prophylactic interventions against HIV-1 infection. With imperfect adherence, intention-to-treat analyses assess the collective effects of complete, sub-optimal and non-adherence, providing a biased and attenuated estimate of the average causal effect of an intervention. Using data from the MTN-020/ASPIRE phase III trial evaluating HIV-1 efficacy of the dapivirine vaginal ring, we conducted per-protocol, and adherence-adjusted causal inference analyses using principal stratification and marginal structural models. We constructed two adherence cut offs of ≥ 0.9 mg (low cutoff) and > 4.0 mg (high cutoff) that represent drug released from the ring over a 28-day period. The HIV-1 efficacy estimate (95% CI) was 30.8% (3.6%, 50.3%) (P = 0.03) from the per-protocol analysis, and 53.6% (16.5%, 74.3%) (P = 0.01) among the highest predicted adherers from principal stratification analyses using the low cutoff. Marginal structural models produced efficacy estimates (95% CIs) ranging from 48.8 (21.8, 66.4) (P = 0.0019) to 56.5% (32.8%, 71.9%) (P = 0.0002). Application of adherence-adjusted causal inference methods are useful in interpreting HIV-1 efficacy in secondary analyses of PrEP clinical trials.